Editors’ Introduction - Sharifah Zahhura Syed Abdullah; Azmi, Zaireeni; Endut, Noraida (Kajian Malaysia, 2020)
Even when the Brundtland Report presented a defining and holistic shift in the way that development had been approached – by centralising human conduct and ethics and framing inclusiveness in development processes, the deeper connection between development and different forms of social inequalities, particularly gender inequality, were not adequately addressed in the document. However, the report was instrumental in becoming the foundation for many key efforts towards relooking at development and operationalising sustainable development, globally. The Brundtland Report’s emphasis on focusing on the “essential needs of the world’s poor” is an important foresight to addressing gender inequality. However, no specific reference to the gender context is made in discoursing poverty alleviation or economic development in the formulation of the sustainable development concept and framework.